Development of high volume POFA self-compacting concrete using colloidal nano silica as a viscosity modifying agent - Kojouri, Samira Jilani (2016)
This study delineates the effects of nano silica on self-compacting concrete (SCC) with high volume replacement of palm oil fuel ash (POFA). POFA is an agro waste found in hefty amounts in Malaysia. It is a by-product of burning residues of palm oil industry which reportedly has pozzolanic behavior. Pozzolanic mineral admixtures are used in concrete to enhance the mechanical properties and the durability. However, the addition of mineral admixtures especially in high volumes reduces the workability and increases the demand for superplasticizer. The negative effect of the explained phenomenon is of great importance in SCC in which high workability as well as cohesiveness is required. Furthermore, inclusion of mineral admixture as a replacement for cement brings about the delay in hydration for which unbound water increases in the matrix at early ages. This increases the risk of segregation and bleeding and as a result the hardened properties of concrete including the mechanical properties and the durability are disadvantageously overshadowed.The overarching purpose of this study was to overcome the above mentioned demerits of inclusion of high volume POFA in the SCC matrix. Accordingly, cement was replaced with 20%, 30% and 50% of POFA to investigate the behavior and reactions at early and late age properties of SCC. Slump flow, J-ring, L-box, and sieve stability test were conducted to assess the fresh properties of SCC with POFA. Also, the compressive strength at ages of 1, 3, 7, 28, and 90 days were recorded. Moreover, the durability tests including chloride permeation, gas permeability, sulfate attack and drying shrinkage were conducted at late ages up to six months. The SEM, XRD, FTIR, TGA, DSC and calorimetry tests were also performed to study the underlying mechanism which the microstructure and chemical composition of samples were changed. The same tests were carried out for samples with 1% colloidal nano silica. For samples with the highest level of replacement (50% POFA), dosages of 0.5% and 1.5% colloidal nano silica were also used.The results showed that the replacement of cement with more than 20% dosage of POFA notably increased the bleeding and segregation of the mixture. The chemical tests ration increased the amount of free water in the matrix. The free water diffused out of the matrix and bleeding and segregation occurred consequently. However, when nano silica was added, the bleeding and segregation were controlled by accelerating the hydration through its pozzolanic and dissolving effects.Furthermore, results from the hardened properties showed that the addition of nano silica compensated the strength depletion caused by high volume of cement replacement,albeit, the target strength of 30 MPa was achieved at 90 days. Similarly, the addition of nano silica reduced the drying shrinkage, gas permeability, sulfate attack and chloride ingression in high volume POFA-SCC. In general, the results were conclusive that the addition of nano silica enhances the properties of self-compacting concrete with high volume of mineral admixture with low cementing properties. Keywords: Self-compacting concrete, POFA, Colloidal nano silica, Stability,Compressive strength, Durability.